Design and Optimization of Fe Doped TiO2 Photocatalytic Reactors for Pollutant Degradation: A Systematic Literature Review - Misriyani Misriyani; Emil Hardiansyah (KOVALEN: Jurnal Riset Kimia, 2026)
Environmental pollution caused by industrial wastewater containing persistent organic compounds has become a major global concern. Photocatalytic technology based on titanium dioxide (TiO2) has attracted significant attention due to its strong oxidation capability, chemical stability, and environmental compatibility. However, the relatively wide band gap of TiO2 limits its activity mainly to ultraviolet light. Metal doping, particularly with iron (Fe), has been widely investigated as a strategy to enhance visible light absorption and suppress electron–hole recombination, thereby improving photocatalytic performance. This study aims to analyze the development and optimization of Fe-doped TiO2 photocatalytic reactors for pollutant degradation through a systematic literature review. The review followed the PRISMA guidelines, and relevant articles were collected from three major scientific databases: Scopus, Web of Science, and ScienceDirect. A total of 166 articles were initially identified, and after screening and eligibility assessment, 18 studies were included in the final analysis. The results show that synthesis methods such as sol–gel and hydrothermal techniques significantly influence catalyst properties and photocatalytic activity. In addition, reactor configurations including packed-bed, fluidized-bed, and photocatalytic membrane reactors play an important role in improving degradation efficiency through optimized light distribution and mass transfer. Reported pollutant degradation efficiencies ranged from approximately 45% to over 99%, depending on operating conditions and reactor design. Despite promising laboratory-scale results, further research is required to improve reactor scalability, catalyst stability, and energy efficiency for large-scale environmental applications.